Pembangunan Pendidikan dan Perubahan Stratifikasi Sosial Masyarakat Desa–Kota di Jawa Timur: Perspektif Modernisasi dan Ketergantungan - Anisa Iskandar; Hendi Irawan (Jurnal Ilmu Sosial dan Humaniora, 2026)
Education development plays a strategic role in improving human resources and promoting social transformation. This study aims to analyze the relationship between educational development and changes in the social stratification of rural–urban communities in East Java from the perspectives of Modernization and Dependency theories. The study employed a qualitative approach using a library research method. Data were collected from secondary sources, including scientific journals, books, research reports, and other relevant academic publications, and were analyzed through descriptive qualitative analysis by synthesizing theoretical and empirical findings. The results indicate that educational development contributes to improving social mobility, expanding employment opportunities, and transforming occupational structures, particularly through the enhancement of human capital. However, educational development has not fully reduced social stratification because disparities in educational access, socioeconomic conditions, and unequal resource distribution between rural and urban areas remain significant. The findings further demonstrate that changes in social stratification cannot be adequately explained by either the Modernization or Dependency perspective alone. Instead, both perspectives complement each other in explaining how educational development simultaneously promotes social mobility while remaining constrained by structural inequalities. Therefore, equitable educational policies are essential to foster inclusive social transformation and reduce disparities between rural and urban communities in East Java..